2016
DOI: 10.3389/fendo.2016.00008
|View full text |Cite
|
Sign up to set email alerts
|

Feeding Problems Are Persistent in Children with Severe Congenital Hyperinsulinism

Abstract: BackgroundCongenital hyperinsulinism (CHI) is a rare but severe disorder of hypoglycemia in children, often complicated by brain injury. In CHI, the long-term prevention of hypoglycemia is dependent on reliable enteral intake of glucose. However, feeding problems (FPs) often impede oral glucose delivery, thereby complicating the management of hypoglycemia. FPs have not been systematically characterized in follow-up in a cohort with CHI.AimsWe aimed to determine the prevalence, types, and persistence of FPs in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 17 publications
2
27
0
1
Order By: Relevance
“…Feeding difficulties occur in a significant proportion of children (33-45%) [59] and are associated with more severe forms of CHI. Feeding difficulties occur in a significant proportion of children (33-45%) [59] and are associated with more severe forms of CHI.…”
Section: Feedingmentioning
confidence: 99%
See 1 more Smart Citation
“…Feeding difficulties occur in a significant proportion of children (33-45%) [59] and are associated with more severe forms of CHI. Feeding difficulties occur in a significant proportion of children (33-45%) [59] and are associated with more severe forms of CHI.…”
Section: Feedingmentioning
confidence: 99%
“…Feeding difficulties, such as sucking and swallowing difficulties, persistent vomiting, gastro-oesophageal reflux and food refusal, represent another burden for families with CHI. Feeding difficulties occur in a significant proportion of children (33-45%) [59] and are associated with more severe forms of CHI. The cause is not clear, but likely to be multifactorial.…”
Section: Feedingmentioning
confidence: 99%
“…Further, oral feeds partly increase insulin secretion, possibly through sensitivity to milk protein triggering insulin, to worsen the risk of hypoglycaemia. This is further complicated by the high rate of feeding problems in patients with CHI . The exact causes for feeding problems in patients with CHI are not clear but are likely to be multifactorial, particularly at a time when children are vulnerable to the stress of illness, painful stimuli, suppression of appetite by high‐concentration dextrose and medication.…”
Section: General Principles Of Hypoglycaemia Correctionmentioning
confidence: 99%
“…Our group has previously found that severity of CHI is a strong predictor for the prevalence of feeding problems (7). Feeding problems can persist beyond resolution of hypoglycaemia in patients with diffuse forms of CHI (6,7) with variations between those undergoing surgery and those treated medically (4). The long-term outcome of feeding problems in CHI has not been characterized.…”
Section: Introductionmentioning
confidence: 99%
“…We did not aim to address predictive factors for development of feeding problems as our group has addressed this previously (7).…”
Section: Introductionmentioning
confidence: 99%